Determinant of small medium business funding decision in Batu city - Anggarani, Dwi; Mas'ud, Muchlis H.; Zulkifli, Zulkifli (MEC-J (Management and Economics Journal), 2018)
This study aims to examine the relationship between determinant variables affecting SME funding decision in Batu City. The approach used is survey research on perpetrators of SMEs excellent products as respondents to test the causality of variables affecting the funding decision. The analysis technique used is multiple regressions. The research found that: (1) although SMEs can achieve profit and increase assets, SMEs in Batu City prioritize internal funding sources. (2) Higher business risk due to increased company size and leverage operations. The SMEs tend to use internal funding rather than debt. SMEs growth does not necessarily use debt. Most the production activities of SMEs in Batu City have reached full capacity.